The Urgency of Halal Tourism Literacy in Responding to Rejection of Halal Tourism in Indonesia - Abdul Rachman; Mayang Ayu Faluthamia; Muhammad Said; Arie Haura (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2022)
Halal tourism has received a rejection from several people in Indonesia because it is understood as a form of Islamization of tourism. This rejection is evidence of the lack of literacy in Halal Tourism in the community regarding Halal Tourism. The purpose of this paper is to investigate the rejection of Halal Tourism in several regions of Indonesia and to discover the important role of Halal Tourism literacy in responding to the rejection of Halal Tourism from some communities. This study used a qualitative descriptive approach using document analysis as a data collection technique. The results of this study indicate that Halal Tourism literacy is very important to be able to increase public understanding of Halal Tourism that the concept of Halal Tourism is a universal concept that can be accepted by all religions, societies, cultures, and governments. Halal Tourism Literacy has an important role to socialize that Halal Tourism is not a form of Islamization of tourism but rather an extended service in the tourism industry in Indonesia.